Facile one-step synthesis of Cu2O@Cu sub-microspheres composites as anode materials for lithium ion batteries. Issue 7 (July 2018) - Zhou, Huijie; Zhao, Hongbin; Zhang, Xuan; Cheng, Hongwei; Lu, Xionggang; Xu, Qian
Abstract: Cu2 O@Cu sub-microspheres composites with a narrow particle size distribution from 300 to 500 nm was successfully fabricated by one-step synthesis through the direct thermal decomposition of copper nitrate (Cu(NO3 )2 ) in octadecylamine (ODA) solvent. As anode materials for lithium ion batteries, the Cu2 O@Cu composites obviously possess high specific capacity, excellent cyclic stability and rate capability. The coulombic efficiency is about 84% in the 1 st cycle and increases significantly up to 97.8% during successive cycles at various current densities. Even under a high current density of 500 mA g −1, the discharge capacity of Cu2 O@Cu composites remains up to 200 mAh g −1 . The excellent electrochemical properties are ascribed to the synergistic effect between high electronic conductivity and volume-buffering capacity of metallic copper composited with Cu2 O.